One-step preparation of SnO2-AuNPs as nanocomposites on photoelectrodes to enhance photoelectrochemical detection of nitrite and superoxide - Li, Qi; Yao, Jingjing; Jiang, Yuning; Guo, Xiaoyu; Ying, Ye; Wen, Ying; Liu, Xinling; Wu, Yiping; Yang, Haifeng; Le, X. Chris (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2022)
[Display omitted] •Photoelectrodes modified with nanocomposites of tin oxide and gold nanoparticles.•SnO2-AuNPs nanocomposites enhanced photoelectric conversion.•Successful photoelectrochemical detection of nitrite and superoxide radicals. The integration of plasmonic metal nanoparticles and semiconductors improves the photoelectric conversion efficiency. We describe here a simple method for preparing photoelectrodes modified with nanocomposites of tin oxide (SnO2) and gold nanoparticles (AuNPs). This preparation process is more convenient, economical, and efficient than the previous methods. The nanocomposite of SnO2-AuNPs on indium tin oxide (ITO) conductive glass electrodes enhanced photoelectric conversion and increased conductivity. The electrodes prepared with SnO2-AuNPs nanocomposites were used as photoanodes in photoelectrochemical methods for the determination of nitrite (NO2−) and superoxide radical (O2−). The detection of superoxide radicals was achieved by stoichiometric conversion of superoxide radicals to nitrite, which overcomes a common problem of chemical instability of superoxide radicals. The photoelectrochemical method for the determination of NO2− had a detection limit of 0.1 nmol/L and a linear dynamic range from 10−9 to 10−5 mol/L. The method was successfully used to assess the photochemical generation of O2− by irradiating a photosensitizer, rose bengal (RB). The photoelectrochemical responses increased with the concentration of the photosensitizer and the time of photo irradiation (532 nm) as expected.